Kompetenzentwicklung durch schulpraktische Übungen - Seifried, Jürgen; Trescher, Andrea (My University, 2007)
Teaching, educating, assessing and innovating (decision of the standing conference of education ministers on 16.12.2004) these areas of competence describe the range of demands placed upon trainee teachers. They should be developed in the context of initial teacher training and continuing professional development. Periods of practical experience in schools allow the students to benefit from a change of perspective (from learner to teacher) and offer, among other things, through the (guided) process of planning, executing and reflecting on their own attempts at teaching, a variety of possibilities for gaining competences. In order to analyse the possibilities offered by periods of practical experience in schools in terms of developing competences, we used the (not uncontroversial) questionnaire by OSER (1997a, 1997b) on standards in teacher training with two cohorts of students at Bamberg University. The questionnaire was handed out before and after the periods of practical school experience respectively, (and a total of 106 students filled it in). It reveals that areas of competence that are closely associated with teaching processes are more likely to change than standards which are located in the administrative realm (for example, school and the public ). Further, the paper details how standards can help improve the quality of teacher training.
Keywords: 370